p16INK4a immunohistochemistry in cervical biopsy specimens: a systematic review and meta-analysis of the interobserver agreement - Reuschenbach, Miriam; Knebel Doeberitz, Magnus von (American journal of clinical pathology, 2014)
Objectives: The interpretation of cervical biopsy specimens guides management of women with suspected cervical cancer precursors. However, morphologic evaluation is subjective and has low interobserver agreement. Addition of p16INK4a immunohistochemistry may improve interpretation. Methods: We performed a systematic review and meta-analysis of published data on interobserver agreement of p16INK4a positivity using p16INK4a immunohistochemistry and of cervical intraepithelial neoplasia grade 2 (CIN2+) and CIN grade 3 (CIN3+) classification using H&E morphology in conjunction with p16INK4a in comparison with H&E morphology alone. Results: The literature search revealed five eligible articles. The results show strong agreement of pathologists’ interpretation of cervical biopsy specimens as p16INK4a positive or negative (pooled κ = 0.90; 95% confidence interval [CI], 0.88–0.92) and significantly higher agreement for a CIN2+ diagnosis with H&E morphology in conjunction with p16INK4a (κ = 0.73; 95% CI, 0.67–0.79) compared with H&E morphology alone (κ = 0.41; 95% CI, 0.17–0.65). Also, a slightly higher agreement for CIN3+ can be observed (κ = 0.66; 95% CI, 0.39–0.94 for H&E morphology in conjunction with p16INK4a and κ = 0.61; 95% CI, 0.44–0.78 for H&E morphology alone), but this difference was not statistically significant. Conclusions: The published literature indicates improved interobserver agreement of the diagnosis of CIN2+ with the conjunctive use of H&E morphology with p16INK4a immunohistochemistry compared with H&E morphology alone.